A Rare Case of Posterior Knee Pain: Synovial Osteochondramatosis - Berke Aras; Ömer Kuzu; Serdar Kesikburun; Evren Yaşar (Galenos Yayinevi, 2021)
Synovial osteochondromatosis (SOC) is an uncommon benign condition characterized by the proliferation of the synovium with cartilaginous metaplasia. It can develop in any joint where synovium exists but is most prevalent in the knee. It generally occurs in the knee's anterior compartment, but it can also be seen in the posterior fossa. In this article, we report a 58-year-old woman with knee pain and swelling secondary to SOC. The detection of calcific nodules in both plain radiography and magnetic resonance imaging of the knee determined the diagnosis. SOC needs attention due to its high morbidity rates and possibility of malignant transformation.